Iron(III) Monoglycerolate as a New Biocompatible Precursor in the Synthesis of Bioactive Nanocomposite Glycerohydrogels - Khonina, Tat'yana Grigor'evna; Tishin, Denis S.; Larionov, Leonid Petrovich; Osipenko, Artur Vasil'evich; Dobrinskaya, Maria Nikolaevna; Bogdanova, Ekaterina Anatol'evna; Karabanalov, Maxim Sergeevich; Bulatova, Maria Alekseevna; Shadrina, Elena Vladimirovna; Chupakhin, Oleg Nikolaevich (Current Pharmaceutical Biotechnology, 2024)
Background: Nanocomposite glycerohydrogels based on biocompatible elementcontaining glycerolates are of practicular interest for biomedical applications. Objective: Using two biocompatible precursors, silicon and iron glycerolates, a new bioactive nanocomposite silicon128;’iron glycerolates hydrogel was obtained by sol-gel method. Methods: The composition and structural features of the hydrogel were studied using a complex of modern analytical techniques, including TEM, XRD, and AES. On the example of experimental animals hemostatic activity of the hydrogel was studied, as well as primary toxicological studies were carried out. Results: The composition of dispersed phase and dispersion medium of silicon128;’iron glycerolates hydrogel was determined. The structural features of hydrogel were revealed and its structure model was proposed. It was shown that silcon-iron glycerolates hydrogel is nontoxic, and exhibits pronounced hemostatic activity. Conclusion: Silicon-iron glycerolates hydrogel is a potential hemostatic agent for topical application in medical and veterinary practice.
Keywords: Silicon glycerolates